Effect of Fenbendazole Treatment Against Oxyuris spp. on Green Iguana (Iguana iguana) - kusuma, shelly; Garvasilus Privantio Tegar Virgiawan Huler; Rafi Dzakir Ghalib; Shafa Luvena Pradhantya; Devita Marsya Herina Hapsari; Nofan Rickyawan; Reza Yesica; Nanis Nurhidayah (IPB University, 2024)
Infection of Oxyuris spp., a gastrointestinal nematode, has been reported in reptiles around the world, including in the green iguana (Iguana iguana). In most cases, parasite control in reptiles relies on anthelmintics administration. Fenbendazole has been used as the drug of choice for parasite control in reptiles. However, the data of fenbendazole administration for Oxyuris spp. infection on green iguana (Iguana iguana) in Indonesia was absent. We evaluated the effect of fenbendazole administration (dose: 25 mg/kg body weight [BW] for five consecutive days per oral) for natural infection of Oxyuris spp. among thirty-three green iguanas in Malang Raya (Malang District, Malang City, and Batu City). The fecal examination was made through a modified Mc Master technique on the day-0, 7, 14, 21, and 31 post-treatment. The data on management (such as caging, feeding, and health program) conducted by the owners were recorded as well. The result showed that reduction of a hundred percent (100%) of egg per gram (epg) on day-31 post-treatment in all sampled animals. Iguanas were placed in individual and communal cages with daily cleaning and feeding. However, none of the owners arranged health programs such as anthelmintic treatment for their companion reptiles. This study can be used as a recommendation for future control of Oxyuris spp. in green iguanas in Indonesia.